2021
DOI: 10.21776/ub.jrm.2021.012.02.21
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rasio I/D terhadap Permulaan Flooding dan Fluktuasi Voltase Sinyal Tekanan Rezim Flooding pada Geometri Kompleks

Abstract: A nuclear power plant operation requires reliability safety systems. Therefore, an accidental scenario such as the LOCA becomes a specific attention. This relates to a countercurrent flow phenomenon which permits the occurrence of a flooding regime. This study aims to investigate the effets of I/D ratios of the riser on the onset of flooding and time-series voltage fluctuations of differential pressure signals of the flooding regime on a complex geometry representing a PWR hot leg. The test section contains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…On the basis of experimental investigations, studies on the basis of visualizations have been largely introduced [2,[5][6][7][8] through detailed identifications of the obtained flow structures. Here, the mechanisms leading to flooding have been visually observed and supported by signal characterizations obtained by physical measurements such as pressures [9,10] as well as phasic fractions [11]. Subsequently, through these visual observations, CCFL has been largely reported to be characterized through a curve representing the phasic superficial velocity when the transition is initiated, well-known as CCFL characteristic curves.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…On the basis of experimental investigations, studies on the basis of visualizations have been largely introduced [2,[5][6][7][8] through detailed identifications of the obtained flow structures. Here, the mechanisms leading to flooding have been visually observed and supported by signal characterizations obtained by physical measurements such as pressures [9,10] as well as phasic fractions [11]. Subsequently, through these visual observations, CCFL has been largely reported to be characterized through a curve representing the phasic superficial velocity when the transition is initiated, well-known as CCFL characteristic curves.…”
Section: Introductionmentioning
confidence: 78%
“…The experiments were carried out during a research framework to investigate the characteristics of counter-current flow in a small-scale facility representing a down-scaled model of German-Konvoi PWR primary circuit [9][10][11][12]13,14]. The experiment apparatus, which is schematically depicted in Figure 1, has been particularly developed in the Laboratory of Fluid Mechanics and Heat Transfers of Universitas Gadjah Mada, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, measurement methods have also been developed to support the corresponding studies. Here, the studies on the pressure fluctuations were reported by several researches [7,8]. Furthermore, the development of measurement methods has been conducted through physical measurements and also measurements on the basis of optical data.…”
Section: International Journal Of Applied Sciences and Smart Technolo...mentioning
confidence: 99%
“…Eksperimental dilakukan untuk menghimpun data berupa hasil rekaman video microbubble dengan menggunakan kamera video kecepatan tinggi Phantom Miro M310 dan data penurunan tekanan pada inlet dan outlet MBG dengan menggunakan Pressure transduser merk Validyne P55D yang kemudian diolah untuk mengetahui performa MBG. Pengolahan data eksperimen berupa probabilitas distribusi ukuran bubble dilakukan dengan menggunakan image processing sedangkan pengolahan data pressure drop dilakukan melalui signal analysis dengan pendekatan statistik untuk mendapatkan hasil yang lebih terperinci [1].…”
unclassified